2014
DOI: 10.1017/s0031182014000316
|View full text |Cite
|
Sign up to set email alerts
|

The intriguing host innate immune response: novel anti-parasitic defence by neutrophil extracellular traps

Abstract: The capacity of polymorphonuclear neutrophils (PMN) and other leucocytes of the innate immune system to expel their DNA in a controlled process into the extracellular environment to trap and kill pathogenic microorganisms led to a paradigm shift in our comprehension of host leucocyte-pathogen interactions. Formation of neutrophil extracellular traps (NETs) has recently been recognized as a novel effector mechanism of the host innate immune response against microbial infections. Meanwhile evidence has arisen th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 70 publications
3
73
0
1
Order By: Relevance
“…We also found that the stimulus for NETs formation provided by spermatozoa is dose dependent and increases over time (Table 1). This agrees with other reports in which NETs formation over time was assessed in bovine spermatozoa (4) and is also confirmed by findings reported in bacteria (18) and parasites (5). A recent report has further found the elimination of human spermatozoa with NETs formation in leukocytospermia and leukocytospermia with bacteriospermia (17).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found that the stimulus for NETs formation provided by spermatozoa is dose dependent and increases over time (Table 1). This agrees with other reports in which NETs formation over time was assessed in bovine spermatozoa (4) and is also confirmed by findings reported in bacteria (18) and parasites (5). A recent report has further found the elimination of human spermatozoa with NETs formation in leukocytospermia and leukocytospermia with bacteriospermia (17).…”
Section: Discussionsupporting
confidence: 92%
“…NETs are released after PMN cell death process, reported as NETosis, and are primarily situated in the extracellular space. NETosis has been shown to be an NADPH oxidase (NOX)-dependent mechanism, which ultimately leads to the extrusion of a mixture of nuclear as well as cytoplasmic granule contents resulting in the formation of DNA-rich web-like structures that are adorned with histones (H1, H2A/H2B, H3, H4) and granular effector molecules, such as neutrophil elastase (NE), pentraxin, lactoferrin, MPO, and others (5,6). Unlike NOXdependent NETosis, NOX-independent NETosis is accompanied by a substantially lower level of ERK activation and a rather moderate level of Akt activation, whereas the activation of p38 is similar in both pathways (7).…”
mentioning
confidence: 99%
“…NET have been shown to be involved in several infections caused by bacteria, viruses and fungi [8-11]. However, little attention has been paid to the role of NET in the early host innate immune response against protozoan parasites [12,13]. By now, NET formation has been described to be induced by some protozoan parasites, such as Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%
“…On the mechanistic level, parasites are immobilized within these DNA-rich structures and may be killed via high local concentrations of antimicrobial molecules [12,13]. Consequently, some cases of parasite-triggered NETosis have been described as ROS-, NE- or MPO-dependent [5,12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…infections (Rose et al 1992a, b;Shi et al 2001a, b;Taubert et al 2008;Hermosilla et al 2014); (iii) these cultures are useful for the screening of pharmaceutical, immunological, or biochemical compounds against Eimeria (Hamid et al 2014;Silva et al 2015); and (iv) it offers the possibility to perform stage-specific analyses at the proteomic or transcriptomic level as demonstrated for E. bovis sporozoiteinfected host cells Lutz et al 2011). Furthermore, this study shows for the first time that infections with E. bovis merozoites I clearly activate bovine host epithelial cells as indicated by the upregulation of the gene transcription of several proinflammatory molecules.…”
Section: Gm-csfmentioning
confidence: 99%